CHOICE TECHNIQUE OF THE EFFICIENCY INDICATORS OF MAINTENANCE SYSTEMS OF AIRCRAFT LAND EQUIPMENT - Богайська, К. (Science-based technologies, 2012)
Main principles of a system effectiveness indexes selection of aviation land engineering maintenance taking into account that their quantitative estimation demands machining of a significant amount of an input information which changes as a function of that in what condition are observed to be a particular copy of aviation land engineering.